Innovative methods in teaching mathematics for college students - Jonuševičienė, Judita; Dreižienė, Lina; Nutautienė, Rasa (Lietuvos matematikos rinkinys, 2012)
This paper describes the concept of teaching methods and their distribution to the various scientific methods, in addition to described innovative teaching methods. Considered innovative teaching methods advantages and disadvantages of teaching mathematics, the math topics examples. College mathematics teachers survey showed that the most applied are traditional methods by integrating into them innovative methods, based on technologies and different methodologies.
Keywords: mathematics; teaching methods; innovative methods